Bevk Perović arhitekti - Perović, Vasa J. (Arhitektura i urbanizam, 2020)
Bevk Perovićarhitekti was founded by Matija Bevk, b. 1972, graduated from Faculty of Architecture University of Ljubljana) and Vasa J. Perović,  b. 1965, graduated from Faculty of Architecture University of Belgrade, YU; Master’s degree from Berlage Institute, Amsterdam). They work, alongside with the international team of 15 young architects, on a diverse range of projects, in different European countries.They have been awarded numerous national and international prizes - European Union Prize for Contemporary Architecture - Mies van der Rohe Emerging Architect Award, Kunstpreis Berlin, Plečnik Prize, Piranesi Award, etc.In order to understand and comprehend their work, one must examine their ‘dedicated choice’ to follow conditions in which a building emerges. These conditions range from political and social, to environmental and material their simple, yet complex architectural solutions strive to answer those conditions beyond bare function.For this publication we have selected two of the most recent finished public buildings: Islamic Religious and Cultural Centre Ljubljana and Neue Galerie und Kasematten / Neue Bastei, Wiener Neustadt 2016 - 2019.
Keywords: Conditions; Recognition; Intervention; Integration; Public space; Detail